Association Between Maximum Standardize Uptake Value and Prognostic Factors at Endometrioid Type Endometrial Carcinoma - Gulseren, Varol; Kocaer, Mustafa; Ozdemir, Isa Aykut; Cakir, Ilker; Gokcu, Mehmet; Gungorduk, Ozgu; Sanci, Muzaffer; Gungorduk, Kemal (Gynecology Obstetrics & Reproductive Medicine, 2020)
Objective: Investigate the relationship between the maximum standardize uptake value (SUVmax) values and the prognostic factors in endometrioid-type endometrial cancer (EEC) patients undergoing preoperative positron emission tomography / computed tomography (PET/CT). Study Design: We reviewed retrospectively the records of patients with EEC diagnosis who underwent hysterectomy in Gynecologic Oncology Clinic of Tepecik Training and Research Hospital between January 2010 and January 2017 in this retrospective study. Receiver operating characteristic (ROC) curve analysis was performed to determine the cut-off values of SUVmax for predicting clinical parameters. The area under the ROC curve (AUC) is presented as a measure of discrimination. Results: It was calculated that the SUVmax values in the uterine tumor were higher and statistically significant in the presence of advanced stage (III-IV), histologic grade III, deep myometrial invasion (≥1 / 2) and large tumor size (≥4 cm) from prognostic factors. The SUVmax values of the groups with and without cervical invasion did not different from each other. In order to use the SUVmax value as a diagnostic test in the ROC analysis, the AUC values were as follows; the grade of advanced stage tumor was 0,685, the grade 3 tumor was 0,797, the depth of myometrial invasion was 0,781, and the size of the large tumor was 0,905. Conclusion: SUVmax value in primary uterine tumor was found to be higher in prognostic factors in patients with advanced stage, high grade, deep myometrial invasion and large tumor.